2009
DOI: 10.1088/0741-3335/51/12/124002
|View full text |Cite
|
Sign up to set email alerts
|

Physics and applications of atmospheric non-thermal air plasma with reference to environment

Abstract: Since air is a natural part of our environment, special attention is given to the study of plasmas in air at atmospheric pressure and their applications. This fact promoted the study of electrical conduction in air-like mixtures, i.e. mixtures containing an electronegative gas component. If the ionization growth is not limited its temporal evolution leads to spark formation, i.e. a thermal plasma of several thousand kelvins in a quasi-local thermodynamic equilibrium state. But before reaching such a thermal st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
75
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(79 citation statements)
references
References 46 publications
(51 reference statements)
4
75
0
Order By: Relevance
“…It is observed that the shielding in the quasi-neutral channel behind the streamer head is of the order of 50% compared to the geometric field. Similar values for the electric field in the plateau of the discharge have been also been observed in [20]. In Figure 6 the electron density when the streamer is in the middle of the gap is presented.…”
Section: Streamer Evolutionsupporting
confidence: 82%
See 1 more Smart Citation
“…It is observed that the shielding in the quasi-neutral channel behind the streamer head is of the order of 50% compared to the geometric field. Similar values for the electric field in the plateau of the discharge have been also been observed in [20]. In Figure 6 the electron density when the streamer is in the middle of the gap is presented.…”
Section: Streamer Evolutionsupporting
confidence: 82%
“…In Figure 6 the electron density when the streamer is in the middle of the gap is presented. The discharge channel that is formed has a radius of approximately 50 µm, a value that is closely dependant on the choice of photoionization radiation model parameters [20], and on the width ( 0 ) of the initial Gaussian plasma spot. For 0 = 25 µm a much narrower streamer was observed in accordance with the results presented in [21].…”
Section: Streamer Evolutionmentioning
confidence: 99%
“…The active species produced in such processes are very important for a multitude of applications, such as biological sterilization and heating, plasma-assisted ignition and combustion, surface treatment, and destruction of harmful substances and pollutants. [1][2][3][4][5][6][7][8][9] It is well known that an admixture of a molecular gas with a noble gas can substantially change the electrical and spectral characteristics of the glow discharge. The degree and trend of these changes typically depend on the discharge conditions, such as the sort of noble gas, sort and percentage of the admixture, gas pressure, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanism of spark breakdown in air at atmospheric pressure is presented in works of Marode. [3,4] The behavior of a point to plane discharge has been analyzed electrically and optically for centimetric gaps in air at atmospheric pressure. It has been shown for both steady and pulsed applied potentials that the evolution always consists of sequence: primary streamer, secondary streamer, dark space (more or less pronounced), and transient arc.…”
Section: Introductionmentioning
confidence: 99%